2023
DOI: 10.1136/jitc-2022-005845
|View full text |Cite
|
Sign up to set email alerts
|

Negative intracellular regulators of T-cell receptor (TCR) signaling as potential antitumor immunotherapy targets

Abstract: Immunotherapy strategies aim to mobilize immune defenses against tumor cells by targeting mainly T cells. Co‐inhibitory receptors or immune checkpoints (ICPs) (such as PD-1 and CTLA4) can limit T cell receptor (TCR) signal propagation in T cells. Antibody-based blocking of immune checkpoints (immune checkpoint inhibitors, ICIs) enable escape from ICP inhibition of TCR signaling. ICI therapies have significantly impacted the prognosis and survival of patients with cancer. However, many patients remain refractor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 176 publications
0
7
0
Order By: Relevance
“…The present study revealed that serum CDC42 at baseline was not significantly decreased in patients with objective response achievement and disease control achievement; PFS and OS after ICI treatment in patients with advanced cervical cancer were decreased in patients with baseline CDC42 ≥600 pg/ml. These findings might be because CDC42 negatively modulated the differentiation of CD8 + T cells, which killed tumor cells following suppression of immune escape by ICI treatment (15,32). As aforementioned, CDC42 was associated with larger tumor size, pelvis metastasis and lung metastasis, which represent higher tumor burden.…”
Section: Discussionmentioning
confidence: 85%
“…The present study revealed that serum CDC42 at baseline was not significantly decreased in patients with objective response achievement and disease control achievement; PFS and OS after ICI treatment in patients with advanced cervical cancer were decreased in patients with baseline CDC42 ≥600 pg/ml. These findings might be because CDC42 negatively modulated the differentiation of CD8 + T cells, which killed tumor cells following suppression of immune escape by ICI treatment (15,32). As aforementioned, CDC42 was associated with larger tumor size, pelvis metastasis and lung metastasis, which represent higher tumor burden.…”
Section: Discussionmentioning
confidence: 85%
“…Additionally, some emerging immune checkpoints are under investigation, such as T cell immunoglobulin and mucin-domain containing-3 (TIM-3), B7 homolog 3 protein (B7-H3), and B7 homolog 4 protein (B7-H4) [ 55 ]. Targeting ICPs (immune checkpoint inhibitors, ICIs) can limit T cell receptor (TCR) signaling [ 56 ]. As a result, ICI therapy has brought significant breakthroughs in cancer immunotherapy for patients [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported the pivotal role of NK and T cell‐mediated cytotoxicity in eliminating cancer cells and its potential in immunotherapy. It is reported that the NK and T cells share some cytotoxic mechanisms, such as the release of perforin and granzymes, which can be effective against cancer cells 35,36 …”
Section: Discussionmentioning
confidence: 99%